Evidence for Magma–Wall Rock Interaction in Carbonatites from the Kaiserstuhl Volcanic Complex (Southwest Germany). (14th May 2019) - Giebel, R J; Parsapoor, A; Walter, B F; Braunger, S; Marks, M A W; Wenzel, T; Markl, G
Abstract: The mineralogy and mineral chemistry of the four major sövite bodies (Badberg, Degenmatt, Haselschacher Buck and Orberg), calcite foidolite/nosean syenite xenoliths (enclosed in the Badberg sövite only) and rare extrusive carbonatites of the Kaiserstuhl Volcanic Complex in Southern Germany provide evidence for contamination processes in the carbonatitic magma system of the Kaiserstuhl. Based on textures and composition, garnet and clinopyroxene in extrusive carbonatites represent xenocrysts entrained from the associated silicate rocks. In contrast, forsterite, monticellite and mica in sövites from Degenmatt, Haselschacher Buck and Orberg probably crystallized from the carbonatitic magma. Clinopyroxene and abundant mica crystallization in the Badberg sövite, however, was induced by the interaction between calcite foidolite xenoliths and the carbonatite melt. Apatite and micas in the various sövite bodies reveal clear compositional differences: apatite from Badberg is higher in REE, Si and Sr than apatite from the other sövite bodies. Mica from Badberg is biotite- and comparatively Fe 2+ -rich (Mg# = 72–88). Mica from the other sövites, however, is phlogopite (Mg# up to 97), as is typical of carbonatites in general. The typical enrichment of Ba due to the kinoshitalite substitution is observed in all sövites, although it is subordinate in the Badberg samples. Instead, Badberg biotites are strongly enriched in IV Al (eastonite substitution) which is less important in the other sövites. The compositional variations of apatite and mica within and between the different sövite bodies reflect the combined effects of fractional crystallization and carbonatite-wall rock interaction during emplacement. The latter process is especially important for the Badberg sövites, where metasomatic interaction released significant amounts of K, Fe, Ti, Al and Si from earlier crystallized nosean syenites. This resulted in a number of mineral reactions that transformed these rocks into calcite foidolites. Moreover, this triggered the crystallization of compositionally distinct mica and clinopyroxene crystals around the xenoliths and within the Badberg sövite itself. Thus, the presence and composition of clinopyroxene and mica in carbonatites may be useful indicators for contamination processes during their emplacement. Moreover, the local increase of silica activity during contamination enabled strong REE enrichment in apatite via a coupled substitution involving Si, which demonstrates the influence of contamination on REE mineralization in carbonatites.